A checklist of the species under the genus Monocystis Von Stein, 1848 (Apicomplexa: Sporozoa: Monocystidae) described from oligochaete hosts - Sarkar, Sutapa; Bandyopadhyay, Probir K. (Zootaxa, 2013)
A checklist of 24 species of the genus Monocystis is presented and includes the salient features of each species, type host and site of infection.